Maternal barriers to stimulating early childhood development on Tidore Island - Kusila, Gilbert Renardi (Indonesian Pediatric Society, 2023)
Background The first 5 years of life provide a foundation for neuroplastic development, which establishes the capacity to accomplish complicated tasks in later life. However, this period is vulnerable to multiple stressors and adversities that prevent children from achieving age-related developmental milestones. Mothers as primary caregivers may find it challenging to engage her child in stimulating activities. Objectives To understand maternal barriers to stimulating early childhood development and potential interventions that can be developed. Methods This explorative, qualitative study was conducted in 13 different service coverage areas of the Soasio Community Health Center (Puskesmas), Tidore Islands, North Maluku, Indonesia. A total of 30 mothers participated in structured interview sessions. The analysis was conducted inductively, by generating some key issues from the interview. Results Eight maternal barriers to engaging in child stimulation activities were found: (1) family members, (2) gender-related interaction, (3) partial understanding of child health-related information, (4) prioritizing one developmental achievement over others, (5) timidity in decision making, (6) delaying stimulation due to overreliance on the role of school, (7) responsive feeding, and (8) media. Maternal motivation, societal awareness of child development, and support of maternal and family mental health are needed to improve maternal engagement in child stimulation. Conclusions Family, community, and life experiences may become maternal barriers to stimulating childhood development. Providing better social support, information access, and woman empowerment in decision-making will help mothers to be more engaged in child development stimulation activities.